Plasma Membrane-Associated Ca2+-Binding Protein PCaP1 is Involved in Root Hydrotropism of Arabidopsis thaliana. (4th March 2019) - Tanaka-Takada, Natsuki; Kobayashi, Akie; Takahashi, Hideyuki; Kamiya, Takehiro; Kinoshita, Toshinori; Maeshima, Masayoshi
Abstract: Root hydrotropism is an essential growth response to water potential gradients in plants. To understand the mechanism, fundamental elements such as MIZU-KUSSEI 1 (MIZ1) have been investigated extensively. We investigated the physiological role of a plasma membrane-associated cation-binding protein (PCaP1) and examined the effect of PCaP1 loss-of-function mutations on root hydrotropism. pcap1 knockout mutants showed a defect in root bending as a hydrotropic response, although gravitropism was normal in pcap1 mutants. When pcap1 seedlings were treated with abscisic acid, a negative regulator of gravitropism, the seedlings showed normal gravitropism. The hydrotropism defect in pcap1 mutants was clearly rescued by introducing the genomic sequence of PCaP1 with an endodermis-specific promoter. Analysis of PCaP1-greenfluorescent protein-expressing roots by confocal laser scanning microscopy revealed that PCaP1 was stably associated with the plasma membrane in most cells, but in the cytoplasm of endodermal cells at the bending region. Furthermore, we prepared a transgenic line overexpressing MIZ1 on the pcap1 background and found that the pcap1 hydrotropism defect was rescued. Our results indicate that PCaP1 in the endodermal cells of the root elongation zone is involved in the hydrotropic response. We suggest that PCaP1 contributes to hydrotropism through a MIZ1-independent pathway or as one of the upstream components that transduce water potential signals to MIZ1.